PENERAPAN MODEL PROBLEM BASED LEARNING DENGAN MEDIA SMARTBOX PADA PEMBELAJARAN IPAS SEBAGAI UPAYA MENINGKATKAN HASIL BELAJAR SISWA KELAS V DI MI ISLAMIYAH 01 KOTA MADIUN - Dewi Yolla Widyastuti; Yulia Diah Safitri; Galuh Andani Nur Indrawangsa; Melik Budiarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The problem faced in this study is the low learning outcomes of fifth grade students of MI Islamiyah 01 Madiun City on the material of Changes in the Earth's Surface, which can be seen from the number of students who have not reached the Minimum Completion Criteria (KKM) at the pre-cycle stage. This condition is caused by the use of conventional learning methods that do not actively involve students, so that understanding of concepts becomes less than optimal. This study aims to improve student learning outcomes through the application of the Problem Based Learning (PBL) model supported by Smartbox media in IPAS learning. The research method used was Classroom Action Research (PTK) with the Kemmis & McTaggart model which was carried out in two cycles. Each cycle consists of planning, implementation, observation, and reflection stages. The research subjects were 27 fifth grade students. Data collection techniques included learning outcome tests, observation, interviews, and documentation. The results showed a significant increase in student learning outcomes after the application of the PBL model assisted by Smartbox. In the pre-cycle, student learning completeness only reached 47.42%. After the action in cycle I, the completeness increased to 68.85% with an average posttest score of 67.77 and in cycle 2 student learning outcomes reached 94.94% with an average score of 80.37. This increase shows that the application of the PBL model with Smartbox media is effective in improving students' understanding and learning outcomes. In addition, student activity and participation during learning also increased, so that the learning process became more meaningful and enjoyable. Thus, the PBL model assisted by Smartbox can be used as an alternative learning strategy to improve student learning outcomes.